2017
DOI: 10.2217/fon-2017-0256
|View full text |Cite
|
Sign up to set email alerts
|

The clinicopathological parameters significance of CD133 and Nestin in epithelial ovarian cancer: a meta-analysis

Abstract: This meta-analysis was conducted to evaluate the association of CD133 and Nestin with epithelial ovarian cancer. Databases (PubMed, EMBASE, Web of Science, China National Knowledge Infrastructure, Wanfang) were searched for relevant studies updated in August 2017. CD133 and Nestin expression were estimated by immunohistochemistry. Statistical analysis was performed by RevMan. A total of 18 studies were included in this meta-analysis. High expression of both CD133 and Nestin was associated with late Internation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 50 publications
2
10
0
Order By: Relevance
“…They may be involved in the manifestation of ovarian cancer, as previously confirmed in borderline ovarian cancer [51], and this may explain the high expression of the marker CD133 in different cancers, including the ovarian tumours found by other studies [37,38,39,40]. In a recent study, Clarkson et al sorted a similar population of small DDX4/ALDH1-positive cells from ovarian cell cultures using fluorescence-activated cell sorting (FACS) using the combined activity of these two markers; they found three different populations of positive cells, two of which were small, ranging from 3 to 10 μm, and developed into primitive follicle-like structures, including oocyte-like cells [62].…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…They may be involved in the manifestation of ovarian cancer, as previously confirmed in borderline ovarian cancer [51], and this may explain the high expression of the marker CD133 in different cancers, including the ovarian tumours found by other studies [37,38,39,40]. In a recent study, Clarkson et al sorted a similar population of small DDX4/ALDH1-positive cells from ovarian cell cultures using fluorescence-activated cell sorting (FACS) using the combined activity of these two markers; they found three different populations of positive cells, two of which were small, ranging from 3 to 10 μm, and developed into primitive follicle-like structures, including oocyte-like cells [62].…”
Section: Discussionmentioning
confidence: 53%
“…Antibodies against this molecule, conjugated to paramagnetic beads or fluorochromes, are powerful biological tools for the isolation of VSELs from adult human tissues [35,36]. Furthermore, this marker is commonly used to isolate cancer stem cells from different types of tumours, including ovarian tumours [37,38,39,40].…”
Section: Introductionmentioning
confidence: 99%
“…CD133 expression was also related to metastasis in lymph nodes in OC. 24 Cioffi et al also obtained the same results which stated that high CD133 expression was significantly associated with advanced FIGO stage on SOC. 25 Wang et al concluded that high expression of CD133 OC was significantly associated with advanced FIGO stage and gave a low survival rate.…”
Section: Discussionmentioning
confidence: 67%
“…Therefore, primary prevention of ovarian cancer is necessary. Although ovarian cancer is confirmed to be associated with many genetic factors [ 4 , 5 ], some dietary factors may also affect the development the risk of ovarian cancer. Dietary vitamin C intake has been linked to many cancers, such as pancreatic cancer [ 6 , 7 ], cervical neoplasia [ 8 ], renal cell carcinoma [ 9 ], esophageal cancer [ 10 ], prostate cancer [ 11 ], and so on.…”
Section: Introductionmentioning
confidence: 99%